Social Media as the Dimension of Contemporary War - Marek Górka (Politeja)
Conflict in the Middle East, after October 7, 2023, has generated an unprecedented amount of visual material in cyberspace. The current war demonstrates how both sides of the conflict and their supporters share a common interest in presenting graphic content to elicit outrage or gain sympathy for their cause. This is understandable, but at the same time, it is important to reveal the true atrocities of the war, including those related to Hamas’s actions on October 7 and the effects of the bombing of the Gaza Strip by Israeli forces. The problem arises when these materials are widely used, leading to a kind of race for increasingly drastic images. Videos and photos enable us to visualise topics that would otherwise be difficult to present. However, the challenge arises when it becomes almost impossible to distinguish between real and fake images.